Effects of compatibilizer on morphology, mechanical and thermal properties of polylactic acid/natural rubber blend [electronic resource] - Nur Syazana Abdullah Sani, 1988-, author 600761 (2015)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2015